Analisis Penerapan Produksi Bersih Dan Pengelolaan Limbah Pada Industri Kerupuk Amplang Skala Kecil Di Kota Singkawang - Farisy, Salman Al; Harnatasya; Hidayat, Riki; Ulya, Novia; Wulan, Putri; Merdekawati, Dewi (CV. SINAR HOWUHOWU, 2025)
This study aims to apply the principles of clean production and waste management systems in household-scale amplang cracker industries in Singkawang City. These industries produce two main types of waste—solid and liquid—which are mostly not optimally managed. The research method used is qualitative descriptive through field observations and documentation. The results show that clean production practices are still limited to spatial separation in production areas, the use of gas fuel, and routine environmental cleanliness. However, waste management remains unintegrated and reactive. Solid waste such as fish bones and scales is discarded without reuse, while liquid waste is directly discharged into open drains without any treatment. Strengthening technical capacity, providing worker training, and adopting simple technologies are necessary to ensure the comprehensive and sustainable application of clean production principles in these small-scale household industries.